Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The role of bile acid in regulating head-kidney, spleen and skin immune function of on-growing grass carp (Ctenopharyngodon idella) - Fei Zhao; Xiu-Rong Peng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

The Phenotypes and Mechanisms of NOTCH2NLC-Related GGC Repeat Expansion Disorders: a Comprehensive Review - Xiu-Rong Huang; Bei-Sha Tang; Peng Jin; Ji-Feng Guo (Molecular Neurobiology, 2022)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

Fluorophenols bearing nitrogenated heterocycle moieties, a class of novel Keap1-Nrf2 protein-protein interaction inhibitors: synthesis, antioxidant stress screening and molecular docking - Xiu E Feng; De Peng Kong; Shu Rong Ban; Rui Ge; Qing Shan Li (Medicinal Chemistry Research, 2019)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Over-expression of ThpI from Choristoneura fumiferana enhances tolerance to cold in Arabidopsis - Bo Zhu; Ai-Sheng Xiong; Ri-He Peng; Jing Xu; Xiao-Fen Jin; Xiu-Rong Meng; Quan-Hong Yao (Molecular Biology Reports, 2010)

Long term sea level change and water mass balance in the South China Sea - Zengrui Rong; Yuguang Liu; Haibo Zong; Peng Xiu (Journal of Ocean University of China, 2009)

Interannual variability of SST, SLA and wind waves in the Hawaii area and their responses to ENSO - Yongcun Cheng; Qing Xu; Yuguang Liu; Chongyin Li; Zengzui Rong; Haibo Zong; Xiu Peng; Xiaobin Yin (Journal of Ocean University of China, 2008)

An analytical algorithm with a wave age factor for altimeter wind speed retrieval - Yongcun Cheng; Qing Xu; Yuguang Liu; Hui Lin; Peng Xiu; Xiaobin Yin; Haibo Zong; Zengrui Rong (International Journal of Remote Sensing, 2008)